Yudi man mga osipon para ki Nunuy asin ki Nini - Arejola, Carlos A.; Billanes, Lorna A.; Abrenica, Boyet (Manila National Commission for the Culture and the Arts, 2009)
A collection of short stories for children.
Children's literature.
In Bikol
Keywords: Children's literature, Philippine; Bikol literature; Phiippine fiction (Bikol) -- Juvenile literature